2012
DOI: 10.1111/j.1740-0929.2011.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing corn with brown rice grain in a total mixed ration silage on milk production, ruminal fermentation and nitrogen balance in lactating dairy cows

Abstract: Nine multiparous Holstein cows were used in a replicated 3 × 3 Latin square design to determine the effects of substituting corn grain with brown rice (BR) grain in total mixed ration (TMR) silage on milk yield, ruminal fermentation and nitrogen (N) balance. The TMR silages were made from the ensiling of TMR containing (dry matter basis) 50.1% forage in rice silage and corn silage combination, and 49.9% concentrate. The grain portion of the diets contained 31.2% steam-flaked corn, 31.2% steam-flaked BR or an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
45
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 25 publications
13
45
3
Order By: Relevance
“…However, significant differences in the DM, EE, NDF, ADF and starch contents of TMR silages were observed (P = 0.029, P = 0.020, P = 0.003, P = 0.036 and P = 0.003, respectively). This result is in agreement with that of Miyaji et al (2012), who prepared TMR silages containing 31.2% steam-flaked BR, 31.2% steam-flaked corn or a 50:50 mixture of BR and corn on a DM basis. These differences of chemical composition are a reflection of differences in these contents of the original grains (Miyaji et al 2010.…”
Section: Results and Discussion Diet Characteristics Of Tmr Silagesupporting
confidence: 92%
See 2 more Smart Citations
“…However, significant differences in the DM, EE, NDF, ADF and starch contents of TMR silages were observed (P = 0.029, P = 0.020, P = 0.003, P = 0.036 and P = 0.003, respectively). This result is in agreement with that of Miyaji et al (2012), who prepared TMR silages containing 31.2% steam-flaked BR, 31.2% steam-flaked corn or a 50:50 mixture of BR and corn on a DM basis. These differences of chemical composition are a reflection of differences in these contents of the original grains (Miyaji et al 2010.…”
Section: Results and Discussion Diet Characteristics Of Tmr Silagesupporting
confidence: 92%
“…The starch content of BR is slightly greater than that of corn grain, and the BR starch is digested more rapidly than the corn grain starch (Enishi et al 2000;Miyaji et al 2010Miyaji et al , 2012. Corn grain is used as the main dietary starch source in dairy cow diets in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was due to the DMI being similar between the dietary treatments and that the diets were isonitrogenous. However, the urinary N excretion and urinary N excretion as a proportion of N intake were less in cows fed high RDS TMR than in cows fed low RDS TMR, and the result was in agreement with the previous studies [22,34]. Ohtani et al [35] showed that supplying more fermentable starch in the diet could increase production of ruminal propionic acid which is a glucose precursor, and then reduce urinary N losses through reducing the amino acids (AA) used for gluconeogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…N retention as a proportion of N was similar between the dietary treatments. This agrees with a previous report [16] and contrasts with other previous reports [20,34]. The inconsistent effects of RDS levels on N retention as a proportion of N can be attributed to the differences of N intake and starch levels.…”
Section: Discussionsupporting
confidence: 88%